Translation techniques analysis of local terms in the abstracts of literature research articles - Noviantina, Irna; Nugroho, Muhammad Aprianto Budie; Suryana, Yayan (Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
As globalization increases the visibility of academic research, the accurate translation of culturally rooted local terms becomes more crucial and challenging. This research investigates the translation techniques and equivalence of local terms in the abstracts of literature research articles, focusing on translations from Indonesian to English. To achieve this goal, a total of 35 abstracts published between 2020 and 2024 were analyzed using a qualitative method with a case study design. The research applied Molina & Albir's 18 translation techniques and examined translation equivalence based on Baker and Nida's frameworks. From the abstracts, 712 data points were collected for analysis. The findings revealed that single techniques were used most frequently used (88.76%), followed by duplet technique (7.16%), triplet technique (3.79%), and quadruplet techniques (0.28%). Among the single techniques, borrowing was the most dominant (72.19%), indicating a strong preference for maintaining local terms in their original form to preserve cultural identity and avoid misinterpretation. Furthermore, in terms of translation equivalence, non-equivalence occurred most frequently (73.60%), while formal equivalence accounted for 23.88%, and dynamic equivalence was the least common (2.53%). These findings suggest that translators often prioritize cultural preservation and face challenges in finding equivalent English terms for Indonesian local terminology, highlighting the complexity and cultural sensitivity required in translating literary abstracts containing local terms.